Towards a conceptual semantic design for mechatronic product's family development - Diagne, Serigne; Coulibaly, Amadou; De Beuvron, Francois (Proceedings of the 2014 International Conference on Innovative Design and Manufacturing (ICIDM), 2014)
Conceptual design is the first step in mechatronic products development process. In this paper, a conceptual semantic design methodology for mechatronic product's family development is proposed. Thus, we go from the specification to a set of classes of solutions satisfying requirements and likely to meet performance constraints such as maintainability, availability, reliability, safety, recyclability. The proposed methodology allows us to take into account the various skills of designers who can participate in the design process. It, also, takes into account the actors that participate to the manufacturing process. This methodology combines collaborative, concurrent, parametric and constraint-based design and is also compatible with V-Model and systematic design.